Insulinlike Growth Factor–Binding Protein-1 Improves Vascular Endothelial Repair in Male Mice in the Setting of Insulin Resistance - Aziz, Amir (Endocrinology, 2017)
Insulin resistance is associated with impaired endothelial regeneration in response to mechanical injury. We recently demonstrated that insulinlike growth factor–binding protein-1 (IGFBP1) ameliorated insulin resistance and increased nitric oxide generation in the endothelium. In this study, we hypothesized that IGFBP1 would improve endothelial regeneration and restore endothelial reparative functions in the setting of insulin resistance. In male mice heterozygous for deletion of insulin receptors, endothelial regeneration after femoral artery wire injury was enhanced by transgenic expression of human IGFBP1 (hIGFBP1). This was not explained by altered abundance of circulating myeloid angiogenic cells. Incubation of human endothelial cells with hIGFBP1 increased integrin expression and enhanced their ability to adhere to and repopulate denuded human saphenous vein ex vivo. In vitro, induction of insulin resistance by tumor necrosis factor α (TNFα) significantly inhibited endothelial cell migration and proliferation. Coincubation with hIGFBP1 restored endothelial migratory and proliferative capacity. At the molecular level, hIGFBP1 induced phosphorylation of focal adhesion kinase, activated RhoA and modulated TNFα-induced actin fiber anisotropy. Collectively, the effects of hIGFBP1 on endothelial cell responses and acceleration of endothelial regeneration in mice indicate that manipulating IGFBP1 could be exploited as a putative strategy to improve endothelial repair in the setting of insulin resistance.